The Developmental Possibilities for Methods of Real Estate and Farm Property Evaluation in Agriculture - Horváth, József (Acta Agraria Debreceniensis, 2004)
Different methods for evaluating property have gained greater importance in agriculture since the change of regime. The open market evaluation could be the best method if the agricultural property had significant turnover, which could serve as a reliable comparison. However, there is no notable turnover, and selling is scarce. And, when there is some, the sales contracts are not available. On the other hand, the open market evaluation is almost the only one assessing method in Western Europe and in the United States. The matrix comparing market data in my methodological development helps to estimate the effects of the elements which determinate real estate value of farms.Another method for evaluating farm property is the discounted future earnings. Enterprises are able to produce series of income continuously during their working periods, which can be considered as perpetuity. This is the base of the discounted future earning evaluation. Determination of income generating capacity is not an easy task. It is also difficult to choose the proper rate of capitalization. If this rate is higher than the usual level, the property will be underestimated. If it is lower, the property will be overrated. According to my calculations the profitability of certain farms of animal breeding may be evaluated under different operating conditions. Furthermore, the capitalisation interest rate may be determined in an objective way.The problem of applying the depreciated replacement cost evaluation method is that there are big deviations among investment costs in tenders of contractors; moreover the estimations of special depreciation forms are rather subjective. One of the process’s greatest difficulties for reliability is that it is doubtful whether depreciated replacement cost could reach the real market value. The utilisation of this method may be spread further in the future by standardising average gross replacement cost of building as well as by measuring depreciation more objectively.